Atypical granular cell tumor in the maxilla: The first report of primary intraosseous granular cell tumor. Issue 8 (16th June 2016) - Oh, Kyu‐Young; Kang, Kyung‐Rim; Yoon, Hye‐Jung; Lee, Jae‐Il; Hong, Sam‐Pyo; Hong, Seong‐Doo
Abstract: Background: Granular cell tumor (GCT) is a benign soft tissue tumor of neural origin and is characterized by eosinophilic granular cells showing positivity for neuronal markers. Herein, we report the first case of primary intraosseous GCT arising in the maxilla of an adolescent girl. Methods and Results: A 16‐year‐old female patient presented with palatal swelling. Radiographic findings revealed a well‐defined radiolucent lesion centrally located in the right maxilla. Mass excision was performed, and histopathologic examination showed sheets and cords of eosinophilic granular cells with cellular pleomorphism. Tumor cells were strongly positive for vimentin, S‐100 protein, and CD56, and negative for cytokeratin, desmin, smooth muscle actin, and c‐kit. High expression of p53 and Ki‐67 was found. The final diagnosis was atypical GCT. Conclusion: When evaluating an intraosseous radiolucent lesion with histopathologic features of granular cells, clinicians and pathologists should include GCT in the differential diagnosis. © 2016 Wiley Periodicals, Inc. Head Neck 38:E2467–E2470, 2016